Território, poder e as múltiplas territorialidades nas terras indígenas e de pretos : narrativa e memória como mediação na construção do território dos povos tradicionais - Silva, Maria Ester Ferreira da (2010)
This thesis presents a discussion about the emergence of the black and indigene territorialities as responsible for a new modality of an agrarian structure that has been building new land access opportunities through the discourse of identity. Black and indigene people based on the clause 68 ADCT (Ato das Disposições Constitucional Transitória Act of the Transitory Constitutional Dispositions) have been organizing themselves through the ethnic narratives and the collective memory in the construction of a struggle space where they try to rebuild old territories or new survival conditions through the use of the land. The historical sense in writing a geography of the defeated is the major feeling that passes by this research. Many were the mechanisms utilized for removing the freedom of speech from indigene and black people. By the plots contrived in the violence of the colonizer process, indigene and black people were silenced and today through the perspective of the narrative directed on the orality they have the opportunity of telling their geographies, their histories, their subjectivities that were destroyed in the will of the colonizer hegemony. When rendering problematic the different territories that comprise the Brazilian territory today, more precisely in the city of Palmeira dos Índios, it is necessary to do a reflexion about the material geography objectified in the terrestrial space, as the geographical discourse about such realities, utilizing itself as for the pretexts that History offers, as science that occupies itself in the remembrance, from the saviour retaking for the word of a past that without it, would disappear in the silence and in the oblivion as also from the Historical Geography understanding that the geographical discourses vary according to the place, according to the society, but mainly according to the time that they were generated. This research inscribes itself in this ambit, it starts from the pretext that the black and indigene people have a lot to tell about the geo-history of the Brazilian territory formation, a history and a geography that is not written in books, not even registered in the means of mass communication (radio, television and cinema), and, therefore is unknown by greater part of population. This new Geography based on the testimonial memory where the dreams not realized and the promises not accomplished, and the displeasures of the present point as methodological possibility, this re-write that is given in layers as a palimpsest open to infinity rereadings and rewriting. In this sense, the seek for another geography of the territory challenges to write the different geographies gathered in the reports from the black and indigene people that had their territories superimposed in the advance of productive forces in the organization of the Brazilian territory. About these absurd and denied geographies by the official historiography emerges the importance of the narrative where the care about the remembrance, either for rebuilding a past that escapes from us, or for guarding anything from death inside our fragile human existence points to the possibilities of reading the histories that humanity tells about itself with the expression from several classes, and from several different times that objectify in the reality.